A case study of transformational leadership and para-police performance in Indonesia. Issue 2 (13th May 2014) - Indrayanto, Adi; Burgess, John; Dayaram, Kandy; ,
Abstract : Purpose: – The purpose of this paper is to investigate and examine the mediating effect of trust and commitment on employees' performance in the context of transformational leadership at Civilian Para-Police Force Institution. Design/methodology/approach: – Leaders and employees at the Civilian Para-Police Force in Indonesia were surveyed and interviewed. Multiple regressions are used to examine and explore the direct and indirect relationship and also provide a model of transformational leadership. Findings: – Transformational leadership does not directly influence towards employee performance; rather trust and commitment are found to be the mediating variables in the relationship between transformational leadership and employee performance. The result supports a model of transformational leadership that is considered to be more effective and suitable for improving performance in para-police organisations. Research limitations/implications: – Limitations include the cross-sectional data analysis, the country and institutional specific focus, and a small sample size ( n =132). Practical implications: – Organisations with similar duties as those of the Indonesian para-police organisation could embrace the suggested transformational leadership model for the purposes of improving organisational performance through maintaining public order, while at the same time avoiding any abuse of social and religious norms, and human rights. Originality/value: – This study provides a detailed account of the effectiveness of transformational leadership for para police organisations in the Indonesian context.